The new expression is 4 times the old expression
The old expression is given as:
A = 3r^2h^2
Rewrite the expression as
A = 3(rh)^2
When rh increases by 100%, the new value of rh becomes
New rh = rh + rh
This gives
New rh = 2rh
So, the equation of the new expression is:
New expression = 3(2rh)^2
Evaluate the exponent
New expression = 3 * 4 (rh)^2
Substitute A = 3(rh)^2 in the above expression
New expression = 4 * A
This gives
New expression = 4A
Hence, the new expression is 4 times the old expression
Read more about expressions at:
https://brainly.com/question/723406
#SPJ1